2024
DOI: 10.3390/biom14040492
|View full text |Cite
|
Sign up to set email alerts
|

Development of Improved Spectrophotometric Assays for Biocatalytic Silyl Ether Hydrolysis

Yuqing Lu,
Chisom S. Egedeuzu,
Peter G. Taylor
et al.

Abstract: Reported herein is the development of assays for the spectrophotometric quantification of biocatalytic silicon−oxygen bond hydrolysis. Central to these assays are a series of chromogenic substrates that release highly absorbing phenoxy anions upon cleavage of the sessile bond. These substrates were tested with silicatein, an enzyme from a marine sponge that is known to catalyse the hydrolysis and condensation of silyl ethers. It was found that, of the substrates tested, tert-butyldimethyl(2-methyl-4-nitropheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…As compound 1 gave the best differentiation between the enzymatic and non-enzymatic reactions, the effect of pH on assays involving this substrate was further investigated, since this experimental parameter can have a significant effect on the fluorescence intensity and enzyme activity. Here, it was found that the best enzyme activity (as evidenced by the highest net reaction rate) occurred at pH 8.5 (Figure 2), which was in agreement with the previous studies 17 . In general, the non-enzymatic rate of hydrolysis was broadly similar across the pH range with only a slight increase towards the higher pH levels.…”
Section: Ph Optimisation Of Assay Withsupporting
confidence: 92%
See 3 more Smart Citations
“…As compound 1 gave the best differentiation between the enzymatic and non-enzymatic reactions, the effect of pH on assays involving this substrate was further investigated, since this experimental parameter can have a significant effect on the fluorescence intensity and enzyme activity. Here, it was found that the best enzyme activity (as evidenced by the highest net reaction rate) occurred at pH 8.5 (Figure 2), which was in agreement with the previous studies 17 . In general, the non-enzymatic rate of hydrolysis was broadly similar across the pH range with only a slight increase towards the higher pH levels.…”
Section: Ph Optimisation Of Assay Withsupporting
confidence: 92%
“…To investigate the utility of these substrates, enzyme assays were carried out using Silα, fused with trigger factor at the N-terminal and a Strep-tag II affinity tag at the C-terminal (henceforth referred to as TF-Silα-Strep), as the model enzyme. Initially, the assays were carried out under the same conditions as the previously reported 4-nitrophenoxy substrates 16,17 . Negative control reactions were also carried out where the enzyme was omitted, to evaluate the stability of each substrate towards aqueous (non-enzymatic) background hydrolysis.…”
Section: Substrate Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Silyl ether substrates encompassing the 4-nitrophenol derivatives have been developed for continuous assays by UV–vis spectrophotometry, , whereby hydrolysis of the Si–O bond results in the release of highly absorbing nitrophenolate ions. However, these anions absorb in the ∼400 nm region (i.e., in the yellow region of the visible spectrum), which also overlaps with the typical absorption spectra and color of crude cell supernatants, so these reagents are therefore unsuitable for screening experiments involving such cell lysates.…”
Section: Introductionmentioning
confidence: 99%